THE EVOLUTION OF THE UZBEKISTAN–AFGHANISTAN BORDER REGIME: ON THE QUESTION OF PERIODISATION (1991–2024) (International Conference on Education, Psychology and Humanities, 2026)
The thesis analyses the changes in the border regime between Uzbekistan and Afghanistan on the basis of normative documents. The author distinguishes five stages of the regime and proposes to treat the border regime as an independent criterion for the periodisation of the history of bilateral relations.
Keywords: Uzbekistan, Afghanistan, border regime, transit, periodisation, Hairatan, Termez, free trade zone.